A STUDY OF HOUSEHOLD BUSINESS AT SAMPE CITA VILLAGE - Rangkuty, Dewi Mahrani; Sajar, Suryani; Yazid, Ahmad; Satria, Wisnu (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Sampe Cita is one of the villages in Kutalimbaru sub-district, Deli Serdang Regency, North Sumatra province, Indonesia. With its natural resources, there are vegetable and fruit crops that become household business opportunities. This study discusses several types of household businesses from the existing village potential so that it becomes an opportunity for business income. This is important to be considered by village officials to support the development of household enterprises in Sampe Cita village.